Effect of Vitamin D Supplementation in Disease Activity, Activity-Related Markers, Inflammatory Marker and Serum Calcium of Systemic Lupus Erythematosus Patiens: A Systematic Review and Meta-Analysis - G Kambayana; Dwijo Anargha Sindhughosa; Pande Ketut Kurniari; Wira Gotera; Yenny Kandarini (Indonesian Journal of Rheumatology, 2021)
Background: Effect of additional supplementation of vitamin D toward Systemic lupus erythematosus (SLE) disease activity still differ in results obtained between studies being conducted. The current meta-analysis systematically analyzed the effect of vitamin D supplementation on SLE disease activity with updated literature, also its effect toward other parameters. Material and Methods: Relevant literatures were obtained from PubMed database and Google Scholar. The obtained studies were analyzed using fixed effect model or random effect model. Results: Five eligible studies with a total of 318 participants were included. Vitamin D supplementation did not affect the total SLEDAI score in SLE patients with pooled mean difference of -0.96 (p =0.09; 95% CI: -2.06 to 0.14). Serum vitamin D level increased after administration of vitamin D with pooled mean difference of 12.67 (p =0.001; 95% CI: 5.04 to 20.29). vitamin D supplementation increase serum calcium levels, with pooled difference of 0.07 (p = 0.006; 95% CI: 0.02 to 0.12). Pooled results from two studies obtained vitamin D supplementation did not affect ESR, C3 and C4. Conclusions: Current meta-analysis obtained no significant changes in SLEDAI scores due to vitamin D supplementation. In contrast, serum vitamin D and serum calcium levels were increased.